Electrochemically stimulating developments in bioelectronic medicine - Sanjuan-Alberte, Paola; Alexander, Morgan R.; Hague, Richard J.M.; Rawson, Frankie J. (Springer, 2018)
Cellular homeostasis is in part controlled by biological generated electrical activity. By interfacing biology with electronic devices this electrical activity can be modulated to actuate cellular behaviour. There are current limitations in merging electronics with biology sufficiently well to target and sense specific electrically active components of cells. By addressing this limitation, researchers give rise to new capabilities for facilitating the twoway transduction signalling mechanisms between the electronic and cellular components. This is required to allow significant advancement of bioelectronic technology which offers new ways of treating and diagnosing diseases. Most of the progress that has been achieved to date in developing bioelectronic therapeutics stimulate neural communication, which ultimately orchestrates organ function back to a healthy state. Some devices used in therapeutics include cochlear and retinal implants and vagus nerve stimulators. However, all cells can be effected by electrical inputs which gives rise to the opportunity to broaden the use of bioelectronic medicine for treating disease. Electronic actuation of non-excitable cells has been shown to lead to ‘programmed’ cell behaviour via application of electronic input which alter key biological processes. A neglected form of cellular electrical communication which has not yet been considered when developing bioelectronics therapeutics is faradaic currents. These are generated during redox reactions. A precedent of electrochemical technology being used to modulate these reactions thereby controlling cell behaviour has already been set. In this mini review we highlight the current state of the art of electronic routes to modulating cell behaviour and identify new ways in which electrochemistry could be used to contribute to the new field of bioelectronic medicine.